A Bayesian stochastic discount factor for the cross-section of individual equity options - Niclas Käfer; Mathis Mörke; Florian Weigert; Tobias Wiest (University of Cologne, Centre for Financial Research (CFR), 2025)
We utilize Bayesian model averaging to estimate a stochastic discount factor (SDF) for single-stock options. A Bayesian model averaging SDF outperforms reduced-form benchmark models in-sample and out-of-sample in pricing option return anomalies and portfolios. We document that the SDF is dense in characteristics with the impliedrealized volatility spread, option return momentum, and jump risk emerging as the most likely included factors. Noteworthy, we find that (i) our results remain largely robust after controlling for transaction costs and (ii) characteristics linked to behavioral biases gain in importance for options with high retail trading volume.
Keywords: G12; G14; C11; C12; C52; C53; 330; Equity options; Option factor models; Asset pricing; Bayesian model averaging